Assessment of zinc uptake by Melastoma malabathricum in soil contaminated with sewage sludge - Patek Mohd, Nur Nazirah; Abdu, Arifin; Jusop, Shamshuddin; Abdul Hamid, Hazandy; Karim, Md. Rezaul; Abdul Malik, Mohammad Nazrin; Basri, Mohd Hadi Akbar; Jamaluddin, Aiza Shaliha (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Heavy metal pollution to the soil environment has become a major source of concern and has posed serious health problems to humans and other ecological systems worldwide. Phytoremediation is a biological treatment where plants are used to remove pollutant from environment. An experiment was conducted to evaluate the potentiality of Melastoma malabathricum as a phytoremediator to absorb heavy metals from soil contaminated with sewage sludge. Melastoma malabathricum seedlings were planted on six different growth media: T0 - Control (100% soil), T1 (80% soil + 20% sewage sludge), T2 (60% soil + 40% sewage sludge), T3 (40% soil + 60% sewage sludge), T4 (20% soil + 80% sewage sludge) and T5 (100% sludge). There were significant difference found in growth parameters and plant biomass. The highest growth performance such as plant height and number of leaves and finally biomass was found in T3. However after harvest, the concentration of Zn in growth medium was decreased due to effective absorption of Zn by Melastoma malabathricum from soil contaminated with sewage sludge and plants were able to accumulate high level of Zn. Therefore, Melastoma malabathricum can be a good accumulator plant due to capability in concentrating contaminants in plant parts.